Clinical significance of plasma c-GMP levels in various hepatobiliary disorders - KANO, Takashi; KAWAI, Hideko; KOJIMA, Takao; Muro, Yasutoshi; TAKAHASHI, Yoshiyata (Kanzo, 1981)
Plasma guanosine 3', 5'-monophosphate (cyclic GMP) were measured by radioimmunoassay in 100 patients with various liver diseases, 24 normal subjects, 16 patients with various types of neoplastic disease and 3 patients with uremia. In patients with acute hepatitis, fatty liver, obstructive jaundice and intrahepatic cholestasis plasma c-GMP levels did not differ significantly from those in normal subjects. In contrast plasma c-GMP were significantly elevated in patients with chronic hepatitis, liver cirrhosis, hepatocellular carcinoma, fulminant hepatitis, various types of neoplastic disease and uremia. The degree of elevation averaged threefold in patients with liver cirrhosis, fourfold in hepatocellular carcinoma and liver cirrhosis with hepatic encephalopathy and sixfold in fulminant hepatitis. In addition significant correlations between plasma c-GMP levels and liver function test (i.e., hepaplastin test, albumin and choline esterase) were observed. Furthermore the measurement of plasma c-GMP levels was useful for the early diagnosis and efficacy of various therapies in patients with hepatocellular carcinoma and fulminant hepatitis. These results suggest that determination of plasma c-GMP is of practical importance for evaluation of severity of hepatocellular damage and malignant transformation and for estimation of hepatic encephalopathy. The mechanism of increased plasma c-GMP content in patients with liver diseases in not clear, although both increased rate of c-GMP production in liver and/or brain tissues and diminished hepatic uptake of c-GMP could be involved.